Pengaruh Penerapan Gaya Mengajar Self Check Style Terhadap Hasil Belajar Gerak Dasar Pada Menendang Bola Dengan Punggung Kaki Dalam Permainan Sepak Bola Pada Peserta Didik Kelas XI SMK Negeri 1 Tomohon - Stive Karundeng; Yuliana Sattu; Djhoni Alfrits Sunkudon (STIKES Columbia Asia Medan, 2025)
Physical education is something that cannot be separated from education in general because physical education fulfills all the goals and functions of education through the development of three aspects, namely cognitive, affective, and psychomotor of the students. Based on observations by the researcher, particularly in the 11th grade, many students still lack understanding and ability in demonstrating the basic movement of kicking a ball with the back of the foot in soccer. The hypothesis in this research is